EFEKTIVITAS METODE PEMBELAJARAN JOYFULL LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PAI DI SD ISLAM DARUL MAKMUR - Primaidola Primaidola; Fajriyani Arsya (ADIBA : JOURNAL OF EDUCATION, 2024)
This research was motivated by problems found in fifth grade students at SD Islam Darul Makmur, namely low student learning outcomes, lack of student mastery of the material, because the method used was still dominated by the lecture method so that students easily felt bored, not serious when following the learning process, not paying attention to the explanation of the material provided by the teacher and this has an impact on student learning outcomes. Most students get unsatisfactory grades. This research aims to determine the effectiveness of using the Joyfull Learning method in improving the learning outcomes of class V.2 students in PAI lessons with SPI elements in Khulafaurrasyidin material at Darul Mamur Sungai Rotan Islamic Elementary School. The research uses a quantitative approach with experimental methods. The research design used was quasi-experimental with a nonequivalent control group pretest-posttest design, namely research involving a control class and an experimental class. The sampling technique uses a purposive sampling technique, namely sampling samples with certain considerations. The data collection techniques used are observation, questionnaires, tests and documentation. Data analysis techniques using normality tests, homogeneity tests and hypothesis tests. The results of the research show that the Joyfull Learning method is effective in increasing student learning outcomes in class V.2 PAI learning in khulafaurrasyidin material at Darul Sungai Rotan Islamic Elementary School.